Faktor-Faktor Penghambat Kesejahteraan Petani Padi Sawah di Desa Sangia Makmur Kecamatan Kabaena Utara Kabupaten Bombana - Musrifin, Agusryawan; Buana, Tjandra; Mardin, Mardin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to determine the inhibiting factors for the welfare of farmers in the village of Sangia Makmur, District Bombana Kabaena Utara District in the village of Sangia Makmur, North Kabaena district, Bombana district. The population in this study was rice farmers. The sampling method was carried out in a simple random sampling of 30 people. Data obtained in this study were analyzed descriptively quantitatively. The inhibiting factor for the welfare of rice farmers in the village of Sangia Makmur is, the variables of the Number of Families, Land Area, and Capital Loans have a significant correlation with welfare. Based on the results of the discussion on the relationship of welfare inhibiting factors to the welfare of lowland rice farmers in Sangia Makmur Village, a conclusion can be drawn that the welfare of paddy rice farmers in Sangia Makmur Village can be categorized as being in the poor line but some farmers are still constrained by the high number of family dependents, loans capital, and land area. Relationship The inhibiting factors for the welfare of lowland rice farmers in Sangia Makmur Village are, the variable amount of family dependents, land area, and capital loans have a significant relationship to the welfare